Improved Solar Thermal Technology For Decarbonising Residential Heating - Fogarty, Cian (School of Physics, Physics, 2023)
The field of solar energy harvesting has emerged over the last number of years as one with considerable scope to provide clean and renewable electricity and heat. Solar Thermal (ST) technology is vital to tackle the pressing issue of CO2-induced global warming. The objective of this project was to investigate if solar thermal collector efficiency could be increased, without increasing the overall cost of the system. This thesis presents a comparison of the energy performance of a market available flat plate solar collector (MFPC) and a novel flat plate solar collector (NFPC) containing a hexadic transparent insulating material (TIM). The fundamental proposition of the dissertation aims to enhance the solar energy uptake in a rear-panel thermal absorber of a solar thermal panel by refining the configuration of the glass enclosure. The objective is to minimize the heat losses to the surroundings by leveraging innovative material engineering and techniques to mitigate convective heat transfer. The energy performance of the two systems was compared experimentally, through FEM analysis, and by transient simulation software in the Irish climate. Results obtained showed that for a range of incident solar insolation of 100 – 1000 W/m2, the NFPC system showed a relative efficiency increase of up to 20.84% over the MFPC. Over a yearlong simulation, the total useful energy gained was 1022.22 kWh and 1237.36 kWh for the 6m2 MFPC and 6m2 NFPC systems respectively. The MFPC required 2465.62 kWh and the NFPC required 2409.37 kWh of additional auxiliary energy to reach the residential required load as per the EN 12976/6 standards. This equated to an average annual solar fraction of 28% for the MFPC and 32% for the NFPC. The annual average collector efficiencies were 40.93% and 49.46% for the MFPC and NFPC respectively. The maximum efficiencies were found to be 65.73% for the MFPC and 79.86% for the NFPC. The efficiency curves were verified experimentally on a lab scale. The inclusion of the hexadic TIM reduced the air circulation speed within the solar collector cavity by 79.16%, producing near stagnant air. An economic analysis of both systems for an average household in Ireland showed that the NFPC system can save a homeowner up to €337.50 more than the current MFPC. This reduces the simple payback period (SPP) from 13.04 years (MFPC) to 10.81 years (NFPC). The inclusion of the hexadic polymer structure also contributed to a 54.54% decrease in the overall weight of the solar thermal collector. The net present value of the NFPC was found to be €764.77 greater than the MFPC making it a more economically attractive system for the public.
APPROVED
Keywords: Decarbonisation, Solar Thermal, Transparent Insulator, Renewable Energy; Nanoscience & Materials; Smart & Sustainable Planet; ENERGY; Energy Materials Sciences; Materials Sciences; Physics; Renewable Energy Sources; THERMAL ENERGY